Guava leaf juice effect towards number of megakaryocytes in bone marrow of thrombocytopenic mice - Nur Atik (Universa Medicina, 2018)
Background Dengue virus infection that most frequently occur in tropical and subtropical regions can cause many symptoms, one of which is a decrease in thrombocyte count. Recent studies showed that guava leaf extract can increase the thrombocyte count in rats. The present study aimed to determine the effect of guava leaf juice in increasing the number of megakaryocytes in the bone marrow of thrombocytopenic mice.